Utilization of the spent catalyst as a raw material for rechargeable battery production: The effect of leaching time, type, and concentration of organic acids - Tabita Kristina Mora Ayu Panggabean; Ratna Frida Susanti; Widi Astuti; Himawan Tri Bayu Murti Petrus; Anastasia Prima Kristijarti; Kevin Cleary Wanta (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This study examines the potential use of the spent catalyst as a raw material for rechargeable batteries. The spent catalyst Ni/γ-Al2O3 still contains relatively high amounts of nickel. This indicates the potential use of the spent catalyst to be leached and purified for synthesizing nickel-based compounds so that it can be applied to rechargeable battery cathodes. In this study, the spent catalyst leaching process employed four types of organic acids: citric acid, lactic acid, oxalic acid, and acetic acid. The spent catalyst was leached under atmospheric conditions and room temperature. Organic acid concentrations were also varied at 0.1, 0.5, 1, and 2 M. The leaching process took place for 240 minutes, where sampling was conducted periodically at 30, 60, 120, 180, and 240 minutes. Experimental results showed that Ni (II) and Al (III) ions were successfully leached to the maximum when using 2M citric acids at a leaching time of 240 minutes. The conditions succeeded in leaching Ni (II) and Al (III) ions of 357.8 and 1,975.4 ppm, respectively. Organic acid, notably citric acid, has excellent potential for further development. Citric acid, as a solvent, has the ability to leach metal ions with high recovery. In addition, this acid is categorized as an eco-friendly and green solvent compared to inorganic acid. Thus, the leaching process can take place without harming the environment.